Microneedles as an Alternative Strategy for Drug Delivery - Morales-FLorido, Isabel Marlen; Miranda Calderon, Jorge Esteban; Gómez Sámano, Miguel Ángel; Escobar-Chavez, Jose Juan (Journal of Pharmacy & Pharmaceutical Sciences, 2022)
The transdermal route has been widely studied in the last decade due to its multiple advantages, where one of the most promising transdermal systems are microneedles, these allow the delivery of drugs in a painless way and with easy application, being very attractive for patients with chronic treatments. This review highlights the new research that develops this approach to transdermal therapies, including examples of materials and methods used for their manufacture and presenting an overview of the clinical trials currently available in Cochrane in a demonstrative way to understand the growing popularity of this strategy.